ANALISIS PERMAINAN GOBAK SODOR DALAM PENDIDIKAN JASMANI - Subagio, Rohmad; Muhyidin, Asep; Mukti Leksono, Suroso; Jamaludin, Ujang (UNIKU PRESS, 2024)
ABSTRACTGobak Sodor game, as one of the traditional Indonesian games, has great potential in improving the quality of physical education in schools. This study aims to analyze the benefits of Gobak Sodor game in developing students' physical, social, and emotional aspects. This type of research is library research, namely a study of theoretical and other research related to values, culture, and norms. The results of the study indicate that Gobak Sodor can improve students' gross motor skills, physical strength, and endurance. In addition, this game also encourages teamwork, strategy, and effective communication among students, as well as helping in character development such as sportsmanship and discipline.